Internal hernia following total gastrectomy with Roux-en-Y reconstruction. - REYNOLDS, JOHN; RAVI, NARAYANASAMY (My University, 2011)
Internal herniation is a well-described complication after a gastric bypass, particularly when performed laparoscopically, although it is rarely described following a total gastrectomy. A 55-year-old lady presented with a 24-hour history of vomiting and rigors 10 months after a radical total gastrectomy with Roux-en-Y reconstruction for a gastric adenocarcinoma. Computed tomography (CT) showed a complete small bowel obstruction and a mesenteric swirl sign, indicating a possible internal hernia. The entire small bowel was found at laparotomy to have migrated through the mesenteric defect adjacent to the site of the previous jejunojejunostomy and was dark purple and aperistaltic. The small bowel was reduced through the defect. At a second laparotomy, the small bowel looked healthy and the defect was repaired. Postoperative recovery was unremarkable. Of numerous signs described, the mesenteric swirl sign is considered the best indicator on CT of an internal hernia following Roux-en-Y reconstruction in gastric bypass surgery. A swirl sign on CT in a patient with abdominal pain should always raise the suspicion of an internal hernia.
PUBLISHED
Keywords: Surgery; Internal herniation; Cancer